ENERGY CONSUMPTION - ECONOMIC GROWTH NEXUS IN NIGERIA: AN EMPIRICAL ASSESSMENT BASED ON ARDL BOUND TEST APPROACH - Dantama, Yusuf Umar; Abdullahi, Yahya Zakari; Inuwa, Nasiru (European Scientific Journal, ESJ, 2012)
This study examines the impact of energy consumption on economic growth in Nigeria over the period 1980-2010. The short-run and long-run relationship between energy consumption variables and economic growth are estimated by using the newly developed autoregressive distributed lag (ARDL) approach to cointegration analysis. The results indicate a long-run relationship between economic growth and energy consumption variables. Although, the coefficient of coal consumption is positive but is statistically insignificant, while both petroleum consumption and electricity consumption have positive and are statistically significant on economic growth. Moreover, the coefficient of error correction model suggests that the speed of adjustment in the estimated model is relatively high and had the expected significant and negative sign.The study therefore recommends that government should strengthening the ongoing transformation agenda particularly on energy infrastructure to create sufficient energy supply. This can be done through service availability, affordability, and accessibility.